Neuropsychological Outcomes in Extremely Preterm Preschoolers Exposed to Tiered Low Oxygen Targets: An Observational Study. (8th December 2015) - Baron, Ida Sue; Weiss, Brandi A.; Baker, Robin; Ahronovich, Margot D.; Litman, Fern R.; Baveja, Rajiv
Abstract: An observational study of neuropsychological outcomes at preschool age of tiered lowered oxygen (O2 ) saturation targets in extremely preterm neonates. We studied 111 three-year-olds born <28 weeks' gestational age. Fifty-nine participants born in 2009–2010 during a time-limited quality improvement initiative each received three-tiered stratification of oxygen rates (83–93% until age 32 weeks, 85–95% until age 35 weeks, and 95% after age 35 weeks), the TieredO2 group. Comparisons were made with 52 participants born in 2007–2008 when pre-initiative saturation targets were non-tiered at 89–100%, the Non-tieredO2 group. Neuropsychological domains included general intellectual, executive, attention, language, visuoperceptual, visual-motor, and fine and gross motor functioning. Descriptive and inferential analyses were conducted. Group comparisons were not statistically significant. Descriptively, the TieredO2 group had better general intellectual, executive function, visual-motor, and motor performance and the Non-tieredO2 group had better language performance. Cohen's d and confidence intervals around d were in similar direction and magnitude across measures. A large effect size was found for recall of digits-forward in participants born at 23 and 24 weeks' gestation, d =0.99 and 1.46, respectively. Better TieredO2 outcomes in all domains except language suggests that the tiered oxygen saturation target method is not harmful and merits further investigation through further studies. Benefit in auditory attention appeared greatest in those born at 23 and 24 weeks. Participants in the tiered oxygen saturation group also had fewer ventilation days and a lower incidence of bronchopulmonary dysplasia, perhaps explanatory for these neuropsychological outcomes at age 3. ( JINS, 2015, 21, 322–331)